Insurance status, stage of presentation, and survival among female patients with head and neck cancer. (22nd March 2019) - Panth, Neelima; Simpson, Matthew C.; Sethi, Rosh K.V.; Varvares, Mark A.; Osazuwa‐Peters, Nosayaba
Abstract : Objectives: Incidence trends and outcomes of head and neck cancer (HNC) among female patients are not well understood. The objective of this study was to estimate incidence trends and quantify the association between health insurance status, stage at presentation, and survival among females with HNC. Study Design: Retrospective cohort study. Methods: The Surveillance, Epidemiology, and End Results database (2007–2014) was queried for females aged ≥18 years diagnosed with a malignant primary head and neck cancer (HNC) ( n = 18, 923). Incidence trends for stage at presentation were estimated using Joinpoint regression analysis. The association between health insurance status and stage at presentation on overall and disease‐specific survival was estimated using Fine and Gray proportional hazards models. Results: Incidence of stage IV HNC rose by 1.24% from 2007 to 2014 (annual percent change = 1.24, 95% CI 0.30, 2.20). Patients with Medicaid (adjusted odds ratio [aOR] = 1.59, 95% confidence interval [CI] 1.45, 1.74) and who were uninsured (aOR = 1.73, 95% CI 1.47, 2.04) were more likely to be diagnosed with advanced stage (stages III/IV) HNC. Similarly, patients with Medicaid (adjusted hazard ratio [aHR] = 1.47, 95% CI 1.38, 1.56) and who were uninsured (aHR =1.45, 95% CI 1.29, 1.63) were more likely to die from any cause compared to privately insured patients. Medicaid (aHR = 1.34, 95% CI 1.24, 1.44) and uninsured (aHR = 1.41, 95% CI 1.24, 1.60) patients also had a greater hazard of HNC‐specific deaths compared to privately insured patients. Conclusions: Incidence of advanced‐stage presentation for female HNC patients in the United States has increased significantly since 2007, and patients who are uninsured or enrolled in Medicaid are more likely to present with late stage disease and die earlier. Level of Evidence: NA Laryngoscope, 130:385–391, 2020